Obvladovanje notranje narave po Radža jogiThe Conquering of Inner Nature according to Rāja Yoga - Milčinski, Maja (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Based on the sources on which the Slovenian translation of Rāja Yoga has been done, this paper presents one of the methods of conquering one's inner nature, namely Rāja Yoga or “the royal yoga”. Although almost all of the schools of Indian philosophy and religion are related to yoga, this paper is focused on the classical yoga, as presented in Patañjali's Yoga sutras and in Swāmī Vivekānanda's (1862-1902) commentaries to them.